2018
DOI: 10.5093/cc2018a11
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la relación entre las verbalizaciones motivadoras y el seguimiento de instrucciones en la terapia psicológica

Abstract: Resumen: En este trabajo se analiza la interacción verbal entre terapeuta y cliente para estudiar las posibles diferencias en el seguimiento de las instrucciones terapéuticas, según vayan acompañadas o no de verbalizaciones motivadoras. Se analizan 38 grabaciones de sesiones clínicas, clasificando las verbalizaciones motivadoras con un sistema de categorías que permite comprobar el tipo específico de verbalización motivadora y la frecuencia con la que son usadas por parte del terapeuta. Los resultados indican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Finally, in total success Socratic questioning fragments, training in reasoning rules tended to appear together with motivating verbalizations that pointed out the consequences that such verbal behaviour will have. These results are consistent with findings from other studies in which it was found that following instructions was more likely when instructions and establishment operations were given together (De Pascual Verdú and Trujillo Sánchez, 2018;Marchena-Giráldez et al, 2013). On the other hand, in the present study it was not found that such sequencing discriminates patients' VAT, or any other type.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, in total success Socratic questioning fragments, training in reasoning rules tended to appear together with motivating verbalizations that pointed out the consequences that such verbal behaviour will have. These results are consistent with findings from other studies in which it was found that following instructions was more likely when instructions and establishment operations were given together (De Pascual Verdú and Trujillo Sánchez, 2018;Marchena-Giráldez et al, 2013). On the other hand, in the present study it was not found that such sequencing discriminates patients' VAT, or any other type.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the limitations of the study, the sample is the first thing to comment on. The size of it was smaller than previous studies of the therapeutic process (i.e., Ruiz-Sancho et al, 2015), although at the same time it was a bit larger than specific studies of verbal MOs (de Pascual-Verdú & Trujillo-Sánchez, 2018). The number of sessions selected was because all cases must have sessions with all the clinically relevant activities, and due to different reasons, not all cases recorded had them.…”
Section: Discussionmentioning
confidence: 93%